Cloning of PsDHN1 gene of Paeonia suffruticosa and waterlogging tolerance analysis of transgenic Arabidopsis with PsDHN1 gene - LIU Huichun; ZHANG Jiaqiang; MA Guangying; ZHOU Jianghua; XU Wenting; ZHU Kaiyuan (浙江大学学报. 农业与生命科学版)
Based on the previous studies, an intermediate sequence of dehydrin gene PsDHN1 was obtained from the leaves of Paeonia suffruticosa and the full-length sequence of PsDHN1 gene was cloned by the rapid-amplification of cDNA ends (RACE) method. In order to explore the characteristics of PsDHN1 and its function in response to waterlogging stress, bioinformatic analysis and transformation into Arabidopsis for functional verification were performed. The results of bioinformatic analysis showed that the full length cDNA of PsDHN1 was 864 bp, containing an open reading frame (ORF) of 471 bp, and the lengths of 5′ and 3′ noncoding regions were 104 bp and 289 bp, respectively. The protein encoded by PsDHN1 gene contained 156 amino acids with the molecular mass of 16.39 kDa, theoretical isoelectric point of 8.87, hydrophilic index of －1.274, belonging to hydrophilic protein, and instability index of 44.05, belonging to unstable protein. The PsDHN1 protein contained three α-helixes and one β-flod, and two Y fragments, one S fragment and two K fragments that belonged to the typical Y2SK2 dehydratin. In addition, the PsDHN1 protein of P. suffruticosa had some homologies with other nine species, among which the similarities between P. suffruticosa and Momordica charantia, Jatropha curcas, Juglans regia were 58%, 54% and 53%, respectively. Subcellular localization results showed that PsDHN1 was mainly localized in the nucleus and cell membrane. The results of waterlogging tolerance test showed that the phenotype of transgenic Arabidopsis plants with PsDHN1 gene had better waterlogging resistance and growth recovery than the wild-type plants. Moreover, the physiological indexes that related to waterlogging tolerance such as sucrose synthase, pyruvate decarboxylase, α-amylase activities and soluble protein content reflected that transgenic Arabidopsis had higher waterlogging tolerance than wild-type plants. The results provide a theoretical basis for mining waterlogging tolerance genes and further research on the molecular mechanisms of P. suffruticosa.